2012
DOI: 10.1007/s12282-011-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

Nipple reconstruction with banked costal cartilage after vertical-type skin-sparing mastectomy and deep inferior epigastric artery perforator flap

Abstract: We recently used skin-sparing mastectomy (SSM), the deep inferior epigastric artery perforator (DIEP) flap, and delayed nipple reconstruction with banked costal cartilage. Eight patients who underwent these reconstructions between 2008 and 2010 were reviewed. SSM was performed by vertical-type incision. We transferred the DIEP flap using an internal thoracic vessel and banked costal cartilage into an abdominal wound. Three to 6 months later, we removed the cartilage and cut it into a cylindrical shape. We fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Cheng et al, 12 Guerra et al, 10 Mori et al, 15 and Heitland et al 11 banked costal cartilage from autologous breast reconstruction and used various forms of flaps to achieve adequate nipple projection. Costal cartilage offers a donor site with minimal surgical morbidity, allowing for a resourceful form of donor tissue and low complaints with regard to subcutaneous banking of the cartilage graft.…”
Section: Costal Cartilagementioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al, 12 Guerra et al, 10 Mori et al, 15 and Heitland et al 11 banked costal cartilage from autologous breast reconstruction and used various forms of flaps to achieve adequate nipple projection. Costal cartilage offers a donor site with minimal surgical morbidity, allowing for a resourceful form of donor tissue and low complaints with regard to subcutaneous banking of the cartilage graft.…”
Section: Costal Cartilagementioning
confidence: 99%
“…Autologous materials include fat, 3,4 cartilage (auricular conchal fossa, costal), [5][6][7][8][9][10][11][12][13][14][15] bone, 16 composite soft tissue including toe pulp, 14,[17][18][19] contralateral nipple, 8,20,21 labia minora, 21,22 and rolled dermal grafts. 23 Reported allogeneic materials have included acellular dermal matrix, [24][25][26][27][28][29] bone allograft, 16 and extracellular matrix collagen.…”
mentioning
confidence: 99%
“…Many plastic surgeons have evaluated the use of local flaps via various methods to improve nipple projection, and are continuously endeavouring to compensate for current shortcomings by investigating the varying effects of alloplastic materials and autologous materials used during nipple reconstruction. However, these materials can lead to potential donor site morbidity, a lengthy operation due to the need for additional surgeries and unanticipated complications caused by the use of the materials .…”
Section: Introductionmentioning
confidence: 99%
“…reported that the reduction rate at 6 months was about 50%, and the reduction rate was reported to be 53%. Several other studies have analysed the long‐term preservation of nipple projection in relation to the breast mound, but the findings remain controversial. To improve surgery outcomes by avoiding these negative outcomes and donor site morbidity while maintaining long‐term nipple projection, we aimed to improve the overall nipple shape and patient satisfaction by using collagen, an alloplastic material, as the main component for reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, adequate maintenance of nipple projection remains a problem faced by plastic surgeons. Numerous nipple reconstruction methods have been introduced, and various materials including cartilage [1], bone [2], fat [3], dermal graft [4], and acellular dermal matrix (ADM) [5] have been used to provide stable long-term projection of the reconstructed nipple. However, reconstructed nipples lose their projection over time, leading to late-onset flattening.…”
Section: Introductionmentioning
confidence: 99%